Analisis Perjalanan Kereta Rel Listrik Pada Lintas Manggarai – Bogor - Jamaludin, Jamaludin; Sadili, Rachmat (Politeknik Perkeretaapian Indonesia Madiun, 2018)
The purpose of this study was to analyze the causes of passenger buildup at the station on the Manggarai - Bogor station. To overcome the buildup of passengers at the station the action that must be taken is to analyze the Headway, cross capacity, the number of trips at this time. The data collected is in the form of the latest number of passengers, the latest number of trips, the latest electric railroad stamformation data. The analysis shows that the current capacity of the electric rail train can only accommodate 455,904 passengers, while the daily passenger volume reaches 460,448 passengers, a difference of 4,544 passengers is found. At present the total electric train travel on the Manggarai - Bogor crossing is 321 Ka / day with a maximum crossing capacity of 403 trains / day. To overcome the problem of accumulation of passengers at the station by adding 2 trips stamformasi electric railroad on the Manggarai - Bogor crossing, looking at the maximum cross capacity in the Manggarai - Bogor crossing, which is 403 trains / day, is still capable of additional trips. The Manggarai - Bogor crossing still uses stamformasi 8, stamformasi 10, stamformasi 12, if it follows the current growth of electric railroad users for stamformasi 8 and stamformasi 10 it cannot cope with the very high number of passengers resulting in passenger transportation exceeding the railroad user comfort standards. electricity. It is recommended to change the information system that operates on Manggarai - Bogor crossroad using 12 information system entirely in order to overcome the problem of passenger buildup at the station